EXAMINING THE IMPACT OF SPECIALIZED HEALTHCARE ROLES AND FACILITY TYPE ON PATIENT OUTCOMES IN NAJRAN, SAUDI ARABIA - Ali Mohammed H Alyami, Hassan Ali Hassan Al-Yami, Hussain Hadi Saleh Al Munajjim, Majed Abdullal Aldhalei, Mohammed Masoud Ali Zubaiyd, Nayef Hadi Saleh Al-Munjam, (Chelonian Research Foundation, 2022)
EXAMINING THE IMPACT OF SPECIALIZED HEALTHCARE ROLES AND FACILITY TYPE ON PATIENT OUTCOMES IN NAJRAN, SAUDI ARABIA Ali Mohammed H Alyami Health Assistant-Health Care security Hassan Ali Hassan Al-Yami Epidemiological Monitor Hussain Hadi Saleh Al Munajjim Health Assistant-Health Care security Majed Abdullal Aldhalei Management of Health Services and Hospitals Mohammed Masoud Ali Zubaiyd Public Health Nayef Hadi Saleh Al-Munjam Health Informatics Technician Abstract The healthcare system in Saudi Arabia has undergone significant reforms in recent years, with a focus on improving patient outcomes and overall quality of care. This study aims to examine the impact of specialized healthcare roles and facility types on patient outcomes in Najran, Saudi Arabia. A retrospective cohort study was conducted using data from various healthcare facilities in Najran, including hospitals and health centers. The study included 1,500 patients who received care from healthcare professionals with different specialized roles, such as health assistants, epidemiological monitors, and health informatics technicians. The primary outcome measures were patient satisfaction, length of stay, and readmission rates. Logistic regression analysis was used to assess the association between healthcare roles, facility types, and patient outcomes, while controlling for potential confounders. The results showed that patients who received care from specialized healthcare professionals in hospital settings had higher satisfaction rates, shorter lengths of stay, and lower readmission rates compared to those treated in health centers. The findings suggest that investing in specialized healthcare roles and improving hospital infrastructure may lead to better patient outcomes in Najran, Saudi Arabia. The study highlights the importance of considering healthcare professional roles and facility types when developing strategies to enhance the quality of care and patient outcomes in the region. Keywords: healthcare roles, facility types, patient outcomes, quality of care, Saudi Arabia